Reference genes validation for qPCR normalization in Deschampsia antarcticaduring abiotic stresses - Lee, Hyoungseok; Kim, Ji Hyun; Park, Mira; Kim, Il-Chan; Yim, Joung Han; Lee, Hong Kum (Antarctic Science, 2010)
Abstract Quantitative real time PCR is the most sensitive and widely used method for the analysis of gene expression. The choice of one or several reference genes is very important for a normalization process, which should not fluctuate under stress conditions, to reduce error rate and bias during experimental procedure. In the present study, the expression stability of nine reference genes (two actins, two tubulins, two elongation factor 1α, two ubiquitins, and cyclophilin) during abiotic stresses such as cold, salt, and PEG treatments, was evaluated on Deschampsia antarctica plants using geNorm software. Results from various experimental conditions indicated that cyclophilin and elongation factor 1α were the most stable genes in the leaf and the root, respectively. The expression of the other reference genes varied under stress. The relative quantification of the TACR7 gene varied according to the kind and the number of reference genes used, suggesting the importance of considering the implications of a combination of reference genes under different stress conditions and in different tissues.